Environmental Ethics Down on the Farm: Hargrove's Weak Anthropocentrism and the "Agricultural Blindspot" - Noll, Samantha (Environmental ethics, 2024)
Eugene Hargrove's impact on the field of environmental philosophy is hard to adequately convey. His service as an activist, educator, and the founder of the journal Environmental Ethics created the context in which the field thrived. His legacy also provides a strong foundation for environmental ethics and activism of the future. Today, environmental philosophy is expanding to include human-dominated environments, once thought to fall outside of the purview of the discipline. Work in these "blind spots" is imperative if we wish to improve sustainability and stem the ecological bleeding that marks the Anthropocene. Hargrove’s theoretical work on "weak anthropocentric intrinsic value" opens a space for environmental ethics to better understand human-dominated environments. If Paul B. Thompson is right that the way we farm should be of utmost concern for environmentalists, then Hargrove's insights could help protect large swaths of land beyond parkland borders.